Diversidad y ecología de Tephritoidea (Insecta: Diptera) en el norte de la Orinoquía colombiana - Herrera-M., Angie Melissa (Universidad de Costa Rica, 2022)
Introduction: Tephritoidea from Colombia are represented by 58 genera and 224 species. In the East of Colombia there is a vast plains region commonly named Orinoquía, belonging to the biogeographic province of Sabana. Despite it biodiversity richness, there are a lack of surveys of insect diversity and there are not systematic collections of flies from Tephritoidea. Objective: The goal of this project was to characterize the Tephritoidea communities (taxonomy and ecological aspects) collected using Multilure traps (McPhail type) baited with hydrolyzed corn protein and to provide information about the economically important species by collecting possible host fruits in two municipalities of the Colombian Orinoquía, Arauca and Saravena (Department of Arauca). Methods: Two sites were sampled in each municipality, a domestic orchard and a forest fragment. Flies were caught weekly from traps or fruits and surveys were carried out from August/2017 to February/2018. Results: A total of 27 species were obtained, twelve of them belonging to family Tephritidae, four to Lonchaeidae and eleven to Richardiidae, six species are new reports from Colombia and seven from the Orinoquia. Diversity index were calculated for studied communities, being diferents between municipalities and areas. Influence of climatic conditions over variability is discussed.  Nine species of fruit flies, that are considered agricultural pests, were found. For these species their relationship with host plants and population dynamic were studied. Conclusions: Anastrepha bezzii, Neotaracia imox, Xanthaciura chrysura, Neosilba batesi, Neosilba zadolicha, Lonchaea longicornis y Lonchaea sp. are reported first time from the department of Arauca and Euarestopsis paupera, Hemixantha lutea, Melanoloma affinis, Melanoloma cyanogaster, Melanoloma varians y Sepsisoma anale from Colombia. Climatic conditions affect diversity and abundance of species being favorable rainy season in driest areas and no rainy in the humid. Anthropic activities influence species diversity.